Awareness, Acceptability, and Perception of Stakeholders on the Vision and Mission of Cavite State University, Teacher Education Department Goals, and Education Program Objectives - Gomez, Anabella C.; Basco, Ma. Corazon M. (Future Science / FSH-PH Publications, 2022)
This descriptive study aimed to determine the extent of awareness of various stakeholders on the Vision and Mission Statements of Cavite State University, Teacher Education Department Goals, and Education Program Objectives (VMGO), the acceptability level of the VMGO statements of the University, and the level of perception on the VMGO’s congruency and alignment to curricular education activities, operations, and projects. The study which was conducted at Cavite State University Imus Campus was able to yield data from 817 internal and external stakeholders. Results reveal that both the internal and external stakeholders are highly aware of the VMGO of the University and its dissemination in various forms of media. Moreover, they highly understand and accept the VMGO statements. Likewise, their perceptions include strong agreement that the VMGO statements are clearly stated and highly congruent and aligned with the University policies and curricular activities of the Teacher Education Department programs.